The Gut Microbe-Derived Metabolite Trimethylamine N-Oxide in Patients With Systemic Lupus Erythematosus: TMAO as a potential biomarker in lupus nephritis. - Mohammed; Shemies, Rasha Samir; Mona; Sarah; Asmaa (Scripta Medica, 2024)
Background/Aim: Both human and animal studies suggest that the gut microbe-derived metabolite trimethylamine N-oxide (TMAO) is strongly associated with several autoimmune diseases including systemic lupus erythematosus (SLE) and correlates to disease severity. The study aimed to investigate the diagnostic and prognostic validity of TMAO as a potential biomarker in patients with SLE, particularly focusing on lupus nephritis patients and its relation to disease activity. Methods: A total of 90 patients were included and assigned into either: group I (SLE without nephritis (NN)), group II (lupus nephritis (LN)) and group III (healthy controls). Serum TMAO levels were compared between the study groups, and correlated to the clinical, laboratory and histopathological criteria. Results: Unpredictably, TMAO levels were significantly higher in healthy controls compared to the total SLE population (p = 0.003), to LN and NN groups individually (p = 0.01). TMAO levels did not significantly vary between (NN) and (LN) patients and only correlated to anti-dsDNA titres (p = 0.02) and red blood cells count (p = 0.02) among LN patients. Conclusion: Contrary to previous studies, TMAO levels were found to be higher in healthy controls. A possible confounding effect of the dietary pattern and ingested drugs on the gut microbiome limits the utility of TMAO as a potential marker in different diseases.